Transnational Models of Citizen Participation: The Case of Participatory Budgeting - Anja Röcke; Carsten Herzberg; Giovanni Allegretti; Yves Sintomer (Journal of Deliberative Democracy, 2012)
This article pursues two main objectives. First, it provides a transnational overview and analysis of participatory budgeting, which has been central to the literature on democratic innovations in citizen participation. Second, it combines this broad empirical project with a theoretical approach based on the construction of ideal-types in the Weberian tradition. Namely, it presents six models of citizen participation: participatory democracy, proximity democracy, participative modernization, multi-stakeholder participation, neo-corporatism, and community development. Although these models have evolved from participatory budgeting and the European context, it is our contention that they can help us to understand the socio-political and ideological dynamics, contexts and impacts of civic engagement and democracy today at the transnational scale.